A COMPARATIVE PROSPECTIVE STUDY OF INTRATHECAL DEXMEDETOMIDINE-FENTANYL FOR LABOR ANALGESIA - Jatale , Amol (Journal of Biomedical and Pharmaceutical Research, 2020)
BACKGROUND: Particularly in developing countries, women have described the intense and frequent pain they endure during childbirth as well as the lack of options for pain management. Sedatives and parenteral opioids are the most regularly prescribed drugs for women in labor in many low-resource settings. It has been shown that his method of treating pain has very little to no effect on the discomfort experienced during birth. Relieving pain during childbirth is one of the primary goals of maternity care. It is generally established that combining spinal and epidural analgesics can reduce labor pain without endangering the mother or fetus. For extended postoperative analgesia, intrathecally administered dexmedetomidine and bupivacaine have been employed. It is an analgesic alpha 2 adrenoreceptor agonist that is very selective. It is highly lipophilic and barely crosses the placenta, according to recent evaluations. AIM: The purpose of the study was to compare the effects of intrathecal fentanyl and dexmedetomidine on the outcomes of mothers and newborns during labor to the effects of either drug alone. MATERIAL AND METHOD: The department of Anesthesia conducted this comparative prospective observational study. All participants gave their informed written agreement regarding their participation in the study and the use of their data for the current research project. One hundred full-term pregnant women who were admitted to the obstetric department for safe confinement were the participants. A tertiary care teaching hospital’s obstetrics department’s dedicated labor room served as the study’s location. A multipara monitor, an ultrasound machine, an anesthetic workstation, and resuscitation supplies are all included in the labor room’s setup. The benefits of labor analgesia have been discussed by the pregnant moms. The consent of an obstetrician was sought before any patient could be included in the study. RESULTS: Out of the 120 patients who met the inclusion criteria, 110 gave their consent and were added to the study when the inclusion criteria were applied. According to the exclusion criteria, ten patients were not accepted. once the 100 patients in the predetermined sample size have been reached. The quality of the block analysis showed that Group A experienced analgesia earlier than Group B. There was statistical significance in the discrepancies. Group A also had analgesia for a longer period of time. Group A exhibits a greater degree of motor block than Group B, according to the examination of motor block. The most frequent adverse effect, according to the analysis of side effects, was pruritus, which was followed by bradycardia, hypotension, shivering, and nausea. CONCLUSION: Intrathecal dexmedetomidine decreases the frequency of side effects and extends the duration of analgesia, in contrast to dexmedetomidine or fentanyl used alone. Intracorneal adjuvant walking epidural is a safe and effective method for labor analgesia. The duration and severity of the block are higher with intrathecal dexmedetomidine. Fentanyl increases the chance of a vaginal birth going well. Fentanyl, not dexmedetomidine, should be utilized as an intrathecal adjuvant for labor analgesia. It provides a longer duration of analgesia with an appropriate level of labor analgesia when compared to fentanyl. KEYWORDS: Labor, Analgesia, Dexmedetomidine, Fentanyl and Neonatal